Melting control of phase change material of semi-cylinders inside a horizontal baffled channel: Convective laminar fluid-structure interaction - Salih, Salah M.; Alsabery, Ammar I.; Hussein, Ahmed K.; Ismael, Muneer; Ghalambaz, Mohammad; Hashim, Ishak (Journal of energy storage)
The problem studied in this paper consists of forced fluid flow inside a horizontal channel involving two semi-cylinders and two flexible baffles attached alternatively to the lower and upper walls of the channel. A phase change material fills the semi-cylinders, which are being heated by constant temperature. Cold air is forced through the channel to induce the contributions of convective and conductive heat transfers, fluid- structure interaction and the melting of phase change material. The prevailing mathematical equations of these physics are normalized and solved using the finite element method with the ALE scheme. The influential parameters are: dimensionless time tau, the elasticity modulus of the baffles E and the Reynolds number Re. The most important results show a retardation of melting volume fraction with increasing Reynolds number and decreasing the elasticity modulus of the flexible baffles. It is found that elevating Re from 10 to 500 and E from 5 x 104 to 5 x 106, the melting volume fraction MVF at tau = 15 reduces by 4.15% and increases by 5.2%, respectively. The flexible baffles having a lower modulus of elasticity augment the Nusselt number very slightly (0.9%), while the pressure drop along the channel decreases notably.